Lao People's Democratic Republic : Poverty Reduction Strategy Paper. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2004)
This paper on the Poverty Reduction Strategy Papers (PRSPs) on the Lao People's Democratic Republic (PDR) explains macroeconomic, structural, and social policies in support of growth and poverty reduction, as well as associated external financing needs and major sources of financing. The Lao PDR's long-term national development goal is to be achieved through sustained equitable economic growth and social development, while safeguarding the country's social, cultural, economic, and political identity. The government's sustained effort to eradicate poverty will become a mass mobilization exercise, empowering local communities and providing a coherent framework for mutually supportive actions by all stakeholders.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet